(untitled) (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
We are pleased to be able to offer this special issue ‘Coloniality, language ideologies, policy and classroom practice in Southern Africa: Malawi, Namibia, Zambia and Zimbabwe, brought together by co-editors Felix Banda, University of the Western Cape and David Sani Mwanza, University of Zambia. And we thank the editors for the work and dedication in bringing this collection to fruition